let [tex]A_i[/tex] be an odd integer, [tex]s_i[/tex] be the square of [tex]a_i[/tex] and [tex]t_i[/tex] be the triangular number, [tex](s_i -1)/8[/tex]. Same for [tex]a_j , s_j, t_j, etc[/tex]. Define Multiplication of [tex]n X A_i , etc[/tex] to be n * s_i - t_j and division to be the reverse of this process. I found that(adsbygoogle = window.adsbygoogle || []).push({});

n X A_i X A_j X A_k = n X A_k X A_j X A_i = n X A_j X A_k X A_i etc.

for instance ((((4 * 9 - 1)*49 - 6)*25 -3) + 1) / 9 = (4*25-3)*49-6 = (4*49-6) * 25 - 3 = B

8*4-1 = 31 and 8*B - 1 = 31*25*49

Is there a simple way to prove this general result?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Novel Multiplication and Division by odd squares

**Physics Forums | Science Articles, Homework Help, Discussion**